Błoński’s Essay Years Later - Głowiński, Michał (Zagłada Żydów. Studia i Materiały, 2008)
The author reflects upon Jan Błoński’s essay “Biedni Polacy patrzą na getto” (Poor Poles look at the ghetto) nearly twenty years of its publication by Tygodnik Powszechny. He points at the innovative character of the depiction of Polish-Jewish issues in the moral context, outside of all the political embroilments. Błoński’s voice is unique, because it acknowledges, in the spirit of the Gospels, that analysis of Polish- -Jewish relations is a fundamental issue for the Polish society, a “homework” that needs to be done. This essay, Głowiński claims, is free from the embroilment in the dualism of the negative and positive myths regarding these relations. The author writes about reactions to this text, the letters to the editor and notes one particular voice, which he reads as an internalised nationalist ideology and the dangerous continuation of the nationalist discourse. Głowiński’s sketch concludes the post scriptum, in which the author refers to another article, published in 2006 by Gazeta Wyborcza, regarding the current historical policy, whose proponents see Błoński’s essay as a negative reference point. The author notes that this essay constantly evokes strong emotions, and, as an expression of critical patriotism, still has its ardent opponents.